Expanding the Frontiers of the Right to Work through Migration: An Evolving Regime - Nnawulezi, Uche; Adeuti, Bosede Remilekun (Brawijaya Law Journal, 2021)
This paper explores the strategic interest in promoting the right to work through migration. Ideally, migrant workers whether under contract or other formal arrangements, or simply setting off on their own initiative should be given a basic understanding of the language, culture, legal, social, and political structures of the states to which they are going. This paper therefore set out to examine why most migrant workers experience challenges in securing employment, while some have to surmount far more barriers either before their departure, or at the time of their admission to the state of employment of all conditions applicable to their admission, as well as of the requirements they must satisfy in the state of employment and the authority to which they must satisfy in the state of employment and the authority to which they must address themselves for any modifications of those conditions. The methodology underpinning the research is essentially descriptive, thus, deductive logical “content analysis” is employed. This paper argues that the consequences of migration and the situation of vulnerability in which migrant workers and members of their families frequently-find themselves cannot only be solved by having a functional fundamental human rights approach on the complexity of social, economics, and cultural issues prevalent in the migration regime. It concludes that with due respect to the author and to his concern for the protection and promotion of the right to work through migration, is to say the least, is a first step towards a sustainable promotion of the right to work through migration.